Intelligent Surveillance for Understanding Events in Urban Traffic Environments - D. Vallejo; F. J. Villanueva; J. A. Albusac; C. Glez-Morcillo; J. J. Castro-Schez (International Journal of Distributed Sensor Networks)
The main goal of intelligent surveillance consists in providing security systems with the skills required for correctly detecting and analyzing events in monitored environments. Since these environments are complex and the information is distributed through them, the use of agent-based approaches has become more and more popular when monitoring moving objects. This paper describes how an existing agent platform has been adopted and used to give support to intelligent surveillance systems. Agents deployed by means of this platform implement a behavior-based model that is flexible enough to deal with the challenges that monitored environments pose. Two case studies of urban traffic environments are discussed to prove the feasibility of the proposal.